2022
DOI: 10.23887/jpi-undiksha.v11i1.34739
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Skills of the Prospective Physical Education Teachers Based on Group Learning Commitment

Abstract: Microteaching focuses on student collaboration efforts to improve teaching skills. Teaching skills are essential for prospective teachers. However, problems still arise because all members are not committed to supporting teaching skills as the ultimate goal of micro-teaching learning. This study aimed to examine differences in the teaching skills of prospective physical education teachers based on group learning. Commitment. This study uses a comparative quantitative design method. The sample involved is 41 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…New ATS publication documents have appeared recently, as confirmed in Phuseengoen & Singhchainara (2022), which seeks to integrate STEM into students' movement and ATS activities. Most recently, developed an ATS instrument for throwing-catch learning, and Blegur, Yustiana, et al (2023) integrated ATS in PE using a scientific learning model to improve student learning outcomes. Seeing the limitations of ATS investigations, the question is whether ATS is not significant in supporting students' self-development.…”
Section: Physical Education In Scopus Databasementioning
confidence: 99%
See 1 more Smart Citation
“…New ATS publication documents have appeared recently, as confirmed in Phuseengoen & Singhchainara (2022), which seeks to integrate STEM into students' movement and ATS activities. Most recently, developed an ATS instrument for throwing-catch learning, and Blegur, Yustiana, et al (2023) integrated ATS in PE using a scientific learning model to improve student learning outcomes. Seeing the limitations of ATS investigations, the question is whether ATS is not significant in supporting students' self-development.…”
Section: Physical Education In Scopus Databasementioning
confidence: 99%
“…Apart from the three studies from the Scopus database, one recent study in 2023 from the Google Scholar database promotes ATS in PE. This study was carried out by Blegur, Yustiana, et al (2023) by integrating ATS into the scientific learning model to improve students' PE learning outcomes. Of the four studies, three, each from the Scopus database and one from the Google Scholar database, confirmed that the investigation of ATS in PE was very limited.…”
Section: Physical Education In Scopus Databasementioning
confidence: 99%
“…Melalui pengamatan yang telah dilakukan terhadap 9 calon guru penjas yang melaksanakan praktek mengajar diketahui beberapa fakta diantaranya adalah media pembelajaran yang digunakan oleh calon guru belum relevan dengan materi pembelajaran yang disampaikan, calon guru belum melakukan penguatan kepada siswa ketika dalam proses menutup pembelajaran, calon guru belum mampu mengembangkan alat penilaian untuk mengukur keberhasilan materi yang disampaikan di kelas. Hasil penelitian serupa mengungkapkan bahwa calon guru sangat diharapkan memiliki keterampilan mengajar, namun ada beberapa permasalahan yang ditemukan yaitu calon guru belum memiliki komitmen dalam rangka mendukung keterampilan mengajar microteaching (Blegur & Lumba, 2022). Pendapat lain mengungkapkan bahwa calon guru dapat mengembangkan keterampilan dasar mengajar sebelum menjadi tenaga pendidik yang diharapkan memiliki kompetensi pedagogik (Ambarawati, 2016).…”
Section: Pendahuluanunclassified
“…Hasil penelitian ini diperkuat oleh pernyataan dari responden A yang mengungkapkan bahwa "Hambatan yang saya alami saat mengikuti perkuliahan microteaching salah satunya adalah kurangnya percaya diri dan belum sepenuhnya bisa menguasai kelas dan berbicara di depan umum dengan lancar". Pernyataan tersebut selaras dengan penelitian terdahulu yang mengungkapkan bahwa kepercayaan diri yang dimiiki oleh individu memberika dampak terhadap keterampilan dalam menyampaikan sesuatu di depan umum (Fatmah et al, 2021) (Blegur & Lumba, 2022). Selain kurangnya rasa percaya diri, calon guru penjas juga mengalami kesulitan untuk menyampaikan materi pembelajaran berdasarkan tingkat pendidikan atau jenjang sekolah.…”
Section: Pembahasanunclassified
“…The collaborative learning process monitored by lecturers has a better effect on learning outcomes (Yudho, 2022). Collaborative learning commitment can help students acquire skills by creating a sense of comfort in learning, reflecting on the responsibility for self-improvement, and seeking to help peers through the role of observer and reflection (Blegur & Lumba, 2022). Students' confidence and happiness and increased selfesteem develop as a result of positive feedback and encouragement from team members (Schulze, 2022) and this applies to collaborative learning.…”
Section: Introductionmentioning
confidence: 99%